4(1.1x+1)=4(1.1x+1)=-2.7+1.5(-8x-1)

Simple and best practice solution for 4(1.1x+1)=4(1.1x+1)=-2.7+1.5(-8x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(1.1x+1)=4(1.1x+1)=-2.7+1.5(-8x-1) equation:



4(1.1x+1)=4(1.1x+1)=-2.7+1.5(-8x-1)
We move all terms to the left:
4(1.1x+1)-(4(1.1x+1))=0
We multiply parentheses
4x-(4(1.1x+1))+4=0
We calculate terms in parentheses: -(4(1.1x+1)), so:
4(1.1x+1)
We multiply parentheses
4x+4
Back to the equation:
-(4x+4)
We get rid of parentheses
4x-4x-4+4=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| k/8+5=17 | | 12(3x5x)x=7 | | 2(4x-2)=3(2x-4) | | 1/2*24=v | | 2y+1=2 | | 3(3+x)-11=8+2x | | 2y+1=22 | | 144+2x=360 | | -3.75=+2(-4x+6.1)-3.25x | | 5=b−2 | | 4(y+4)=-9 | | 15+6x=45-15 | | 16u-7u=36 | | -4X+6-7x+9=18 | | -4n+3=22.5 | | -8x+16=-6 | | -4X+6+7x+9=18 | | 9=0.6r | | 4.9x^2+x-80=0 | | 9=0.4r | | 5x-5x=-3(8x+6)-7(x-7) | | -8/7=1/2x-5/3 | | 9x+4x+x= | | 7(-4)+4y=8 | | 3(x+10)=3(x-1) | | -6(x-6)=30-5x | | -25=-24u | | 7x+2(-7+2x)=10+3x | | R=250m | | -3+y/6=-11 | | 3/5w-3/2=-5/3 | | 5x+8x=-10+8x |

Equations solver categories